Paracoccidioidomycosis Associated With a Heterozygous STAT4 Mutation and Impaired IFN-gamma Immunity - Schimke, Lena F.; Hibbard, James; Martinez-Barricarte, Ruben; Khan, Taj Ali; Cavalcante, Ricardo de Souza [UNESP]; Oliveira Junior, Edgar Borges de; Franca, Tabata Takahashi; Iqbal, Asif; Yamamoto, Guilherme; Arslanian, Christina; Feriotti, Claudia; Costa, Tania Alves; et al. (Oxford Univ Press Inc, 2017)
Background. Mutations in genes affecting interferon-gamma (IFN-gamma) immunity have contributed to understand the role of IFN-gamma in protection against intracellular pathogens. However, inborn errors in STAT4, which controls interleukin-12 (IL-12) responses, have not yet been reported. Our objective was to determine the genetic defect in a family with a history of paracoccidioidomycosis. Methods. Genetic analysis was performed by whole-exome sequencing and Sanger sequencing. STAT4 phosphorylation (pSTAT4) and translocation to the nucleus, IFN-gamma release by patient lymphocytes, and microbicidal activity of patient monocytes/macrophages were assessed. The effect on STAT4 function was evaluated by site-directed mutagenesis using a lymphoblastoid B cell line (B-LCL) and U3A cells. Results. A heterozygous missense mutation, c.1952 A > T (p.E651V) in STAT4 was identified in the index patient and her father. Patient's and father's lymphocytes showed reduced pSTAT4, nuclear translocation, and impaired IFN-gamma production. Mutant B-LCL and U3A cells also displayed reduced pSTAT4. Patient's and father's peripheral blood mononuclear cells and macrophages demonstrated impaired fungicidal activity compared with those from healthy controls that improved in the presence of recombinant human IFN-gamma, but not rhIL-12. Conclusion. Our data suggest autosomal dominant STAT4 deficiency as a novel inborn error of IL-12-dependent IFN-gamma immunity associated with susceptibility to paracoccidioidomycosis.
Keywords: STAT4 deficiency; primary immunodeficiency; IL-12/IFN-gamma axis; paracoccidioidomycosis